2013
DOI: 10.1177/2150135113501901
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid Aortic Valves Experience Increased Strain as Compared to Tricuspid Aortic Valves

Abstract: Objective: To determine whether the leaflets of bicuspid aortic valve (BAV) experience increased strain when compared to tricuspid aortic valve (TAV) leaflets. Background: The population at highest risk of aortic valve calcification (AVC) are individuals with BAVs. Currently, efforts to medically treat AVC are hampered by a limited understanding of the biomechanical forces involved in the molecular pathogenesis of AVC. Methods: Surgically created BAVs and control TAVs were placed into a left heart simulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Given this disorganization, isotropic strain is a starting point to examine the stretch responsive molecular pathways in BAV AVICs. Anisotropic strains are an interesting topic to study because we have found that BAVs experience anisotropic strains in ex vivo experiments (13). In addition, there are interesting data that porcine AVICs have differential responses to anisotropic strain (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this disorganization, isotropic strain is a starting point to examine the stretch responsive molecular pathways in BAV AVICs. Anisotropic strains are an interesting topic to study because we have found that BAVs experience anisotropic strains in ex vivo experiments (13). In addition, there are interesting data that porcine AVICs have differential responses to anisotropic strain (53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are interesting data that porcine AVICs have differential responses to anisotropic strain (53). Although we have found BAV leaflets can experience as high as 25% increase in strain (13), a 14% strain for our experiments was used because that was the maximum strain that the Flexcell system could deliver at 1 Hz. Exposing human AVICs to anisotropic strains and different magnitudes of strain has potential to further the understanding of the role that stretch plays in the pathogenesis of BAV calcification.…”
Section: Discussionmentioning
confidence: 99%
“…One is the susceptibility of the bicuspid aortic valve (BAV) to valve calcification (Michelena et al 2014); BAV is a congenital valve defect in which the patient has only two aortic valves, while a normal person has three. BAVs experience more hemodynamic stress, which can increase the risk of developing CAVD (Szeto et al 2013). The other example is the side-dependent pathological characteristics of CAVD.…”
Section: Introductionmentioning
confidence: 99%
“…BAVs are under a significantly higher amount strain compared to tricuspid aortic valves, and increased mechanical stress on VICs contributes to cell injury in AVC (Merryman and Schoen 2013;Szeto et al 2013). Activation of VICs by shear stress induces inflammatory events and angiogenic activity.…”
Section: Discussionmentioning
confidence: 99%